Assessing Spatial Audio: A Listener-Centric Case Study on Object-Based and Ambisonic Audio Processing - MAŁECKI, Paweł; STEFAŃSKA, Joanna; SZYDŁOWSKA, Maja (Archives of Acoustics, 2024)
The research explores the production and critical evaluation of two distinct mixes of “Dancing Ends”, a musical composition by Łukasz Pieprzyk. These mixes were engineered using two cutting-edge spatial sound technologies: Dolby Atmos and Ambisonics. The recording process incorporated overdub and multitrack recording techniques. Once created, the mixes were evaluated using a method of direct rating, based on an average rank system from 1 to 5, adhering strictly to the (ITU-R, 2015) BS.1116-3 and (ITU-R, 2019) BS.1284-2 standards. Evaluation criteria included factors such as mix selectivity, depth, width, and height of the sound stage, sound envelopment, tonal brightness, and quality of source localization. Additionally, some criteria were specifically tailored to evaluate characteristics unique to the composition. The evaluations were performed on three different listening systems and environments: surround systems of 5.1 and 7.1.4, and binaural listening. Although Ambisonics’ mix received higher ratings in several categories, Dolby Atmos’ mix was preferred across all listening environments. The results underscore the potential benefits of employing spatial sound technologies in music production and evaluation, offering insight into the capabilities of Dolby Atmos and Ambisonics.